Pewna Metoda Przybliżonego Obliczania Dwuwymiarowych Zagadnień Dyfuzji - Z. Thrun (Engineering Transactions)
The note presents a method of approximate solution of initial and boundary value problems is a great conduction of heat in two-dimensional, nonhomogeneous and anisotropic regions. There is a great accuracy in the results reached by this approximate method of solution, therefore the first approximation is usually sufficient for practical problems. In two dimensional problems the approximate one solution is assumed in form of a product of two initially assumed function of one functions: one space variable only, and the second - unknown function of a space variable and a time variable. orthogonality conditions a system of differential equations is then derived, the solution of which produces the unknown functions. The method is illustrated by three examples in different coordinate systems.